DEVELOPMENT OF A LABORATORY MODEL IN ECONOMIC EDUCATION - Nuzulul (Oikonomia : Journal of Management Economics and Accounting, 2023)
The laboratory is a necessity needed by all study programs to support the smooth learning process, including the Economic Education study program. In this study, the authors used a research method known as library research, which is a series of activities in line with the data collection methodology. In this research, the author uses a type of research known as library research which is a sequence of actions that follow data collection techniques. According to Abdul Rahman Sholeh, library research is research that uses techniques to collect information by placing the facility at the center and only contains research that connects to the research objectives.  Laboratory-based education helps students understand concepts more easily, facilitate understanding of the material presented to them, strengthen understanding of related material, and develop critical thinking skills.